Modern family. the complete tenth season [videorecording (DVD)]. - O'Neill, Ed, 1946-; Vergara, Sofía, 1972-; Bowen, Julie; Burrell, Ty, 1967-; Ferguson, Jesse Tyler; Stonestreet, Eric, 1971- (Universal Pictures Home Entertainment, 2019)
As the tenth season kicks off, Jay's slated to be grand marshal in a Fourth of July parade, prompting the Pritchett-Dunphy-Tuckers to set off a few too many fireworks. Phil stumbles into a new career opportunity, while Claire grapples with her potentially changing role in the family. Meanwhile, Gloria obsesses over Manny's relationship and Joe's extracurricular activities. The extended family deals with death, but they also evolve, with more laughs than ever.